2019
DOI: 10.3390/cells8121610
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin Is Critical for the Survival of Germ Cells, the Formation of Steroidogenic Cells, and the Architecture of Developing Mouse Gonads

Abstract: Normal gonad development assures the fertility of the individual. The properly functioning gonads must contain a sufficient number of the viable germ cells, possess a correct architecture and tissue structure, and assure the proper hormonal regulation. This is achieved by the interplay between the germ cells and different types of somatic cells. N-cadherin coded by the Cdh2 gene plays a critical role in this interplay. To gain an insight into the role of N-cadherin in the development of mouse gonads, we used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…The mouse embryos with a mutation in E-cadherin or N-cadherin die at the 32-cell stage and E10 stage, respectively [64,65]. To overcome the lethality, we performed conditional knockouts of E-or N-cadherin in the germ cells or somatic cells of developing mouse gonads [62,66].…”
Section: Cadherins In Gonad Developmentmentioning
confidence: 99%
“…The mouse embryos with a mutation in E-cadherin or N-cadherin die at the 32-cell stage and E10 stage, respectively [64,65]. To overcome the lethality, we performed conditional knockouts of E-or N-cadherin in the germ cells or somatic cells of developing mouse gonads [62,66].…”
Section: Cadherins In Gonad Developmentmentioning
confidence: 99%
“…We also performed a weighted gene co-expression network analysis on our sequencing results, looked for modules that are synergistically expressed, and explored the hub genes in the regulatory network. We found that many hub genes such [25,29].…”
Section: Discussionmentioning
confidence: 77%
“…N-cadherin coded by the Cdh2 gene is important for maintenance of the testis cord structure and is required for the formation of steroidogenic cells. N-cadherin plays a major role in gonad differentiation, structuralization, and function [25]. Disruption of the spermatogenic cell-specific mouse enolase 4…”
Section: Co-expression Network Analysis Identified Several Hub Genes mentioning
confidence: 99%
“…The knockout of N-cadherin in the germ cells led to apoptosis, and reduction of germ cell number [55]. The knockout of N-cadherin in gonadal somatic cells, in contrast to the E-cadherin knockout, disrupted the gonad structure.…”
Section: Cadherins In Gonad Developmentmentioning
confidence: 96%
“…The mouse embryos with a mutation in E-cadherin or N-cadherin die at the 32-cell stage, and E10 stage, respectively [53,54]. To overcome the lethality, we performed conditional knockouts of E-or N-cadherin in the germ cells or somatic cells of developing mouse gonads [51,55].…”
Section: Cadherins In Gonad Developmentmentioning
confidence: 99%